A collaborative approach to develop an intervention to strengthen health visitors’ role in prevention of excess weight gain in children - Devashish Ray; Falko Sniehotta; Elaine McColl; Louisa Ells; Gill O’Neill; Karen McCabe (BMC Public Health, 2022)
Abstract Background The high prevalence of childhood obesity is a concern for public health policy and practitioners, leading to a focus on early prevention. UK health visitors (HVs) are well-positioned to prevent excessive weight gain trends in pre-school children but experience barriers to implementing guideline recommended practices. This research engaged with HVs to design an intervention to strengthen their role in prevention of early childhood obesity. Methods We describe the processes we used to develop a behaviour change intervention and measures to test its feasibility. We conducted a systematic review to identify factors associated with implementation of practices recommended for prevention of early childhood obesity. We carried out interactive workshops with HVs who deliver health visiting services in County Durham, England. Workshop format was informed by the behaviour change wheel framework for developing theory-based interventions and incorporated systematic review evidence. As intended recipients of the intervention, HVs provided their views of what is important and acceptable in the local context. The findings of the workshops were combined in an iterative process to inform the four steps of the Implementation Intervention development framework that was adapted as a practical guide for the development process. Results Theoretical analysis of the workshop findings revealed HVs’ capabilities, opportunities and motivations related to prevention of excess weight in 0-2 year olds. Intervention strategies deemed most likely to support implementation (enablement, education, training, modelling, persuasion) were combined to design an interactive training intervention. Measures to test acceptability, feasibility, and fidelity of delivery of the proposed intervention were identified. Conclusions An interactive training intervention has been designed, informed by theory, evidence, and expert knowledge of HVs, in an area of health promotion that is currently evolving. This research addresses an important evidence-practice gap in prevention of childhood obesity. The use of a systematic approach to the development process, identification of intervention contents and their hypothesised mechanisms of action provides an opportunity for this research to contribute to the body of literature on designing of implementation interventions using a collaborative approach. Future research should be directed to evaluate the acceptability and feasibility of the intervention.